Modern approaches to diagnostics of osteoporosis and ischemia in women after menopause under conditions of primary medical and sanitary aid. - T. V. Bugrim (Medičnì Perspektivi, 2014)
Problem of osteoporosis has gained a special significance especially in the last years’ period. In postmenopausal period women suffer not only from osteoporosis (OP) but of increased incidence of cardiovascular diseases, including ischemic heart disease (IHD). The aim of this investigation was to carry out the diagnostics of OP and ischemic manifestation in women of postmenopause period by modern methods. 85 women aged 45-65 years with physiological and pathological climax were included in the investigation. Diagnostic of OP was carried out basing on the bone mineral density evaluation by X-ray Duoenergetic absorption. Diagnostic of IHD was carried out by veloergometry, evaluating stenocardia clinical manifestations and functional class. As a result it was established that 57,1% women in a postmenopausal period suffered both from osteoporosis and ischemic heart disease. Diagnostic of OP and IHD confirmed presence of changes in bone and cardiovascular systems in all examined women.